Sex‐Specific Differences in Survival and Heart Failure Hospitalization After Cardiac Resynchronization Therapy With or Without Defibrillation. Issue 22 (19th November 2019) - Leyva, Francisco; Qiu, Tian; Zegard, Abbasin; McNulty, David; Evison, Felicity; Ray, Daniel; Gasparini, Maurizio
Abstract : Background: Women are underrepresented in cardiac resynchronization therapy (CRT) trials. Some studies suggest that women fare better than men after CRT. We sought to explore clinical outcomes in women and men undergoing CRT‐defibrillation or CRT‐pacing in real‐world clinical practice. Methods and Results: A national database (Hospital Episode Statistics for England) was used to quantify clinical outcomes in 43 730 patients (women: 10 890 [24.9%]; men: 32 840 [75.1%]) undergoing CRT over 7.6 years, (median follow‐up 2.2 years, interquartile range, 1–4 years). In analysis of the total population, the primary end point of total mortality (adjusted hazard ratio [aHR], 0.73; 95% CI, 0.69–0.76) and the secondary end point of total mortality or heart failure hospitalization (aHR, 0.79, 95% CI 0.75–0.82) were lower in women, independent of known confounders. Total mortality (aHR, 0.73; 95% CI, 0.70–0.76) and total mortality or heart failure hospitalization (aHR, 0.79; 95% CI, 0.75–0.82) were lower for CRT‐defibrillation than for CRT‐pacing. In analyses of patients with (aHR, 0.89; 95% CI, 0.80–0.98) or without (aHR, 0.70; 95% CI, 0.66–0.73) a myocardial infarction, women had a lower total mortality. In sex‐specific analyses, total mortality was lower after CRT‐defibrillation in women (aHR, 0.83; P =0.013) and men (aHR, 0.69; P <0.001). Conclusions: Compared with men, women lived longer and were less likely to be hospitalized for heart failure after CRT. In both sexes, CRT‐defibrillation was superior to CRT‐pacing with respect to survival and heart failure hospitalization. The longest survival after CRT was observed in women without a history of myocardial infarction.